Report On The Acculturation Of Potential World Class Research Programmes At Usm. - Advisory, Advisory Committee To The Vice Chancellor Report (Pejabat Naib Canselor, 2001)
1. Introduction 1.1 The Vice Chancellor outlined his vision that USM will be · a research-based teaching university, working towards world class research and academic programmes. To this end he appointed a professorial committee comprising five senior professors to conduct an in-dept audit and submit a report for further action. 1.2 A world class programme is taken to mean a programme which appears to be at the cutting edge of scientific and/or technological discovery generating innovative high impact products or scholarly activity. 1.3 The move towards making USM a world class university is by transforming USM into a research-intensified university. 2. Terms of Reference 2.1 The Committee was responsible for assessing submitted programmes for impact and sustainability of research activities and also to identify programmes which have potential to be nurtured as world class programmes. 2.2 The Committee considered teaching and research as the two major functions of the university. But for the purposes of this report the Committee will focus only on research activities. 3. Criteria for Excellence 3.1 The Committee Identified two major criteria that world class programmes have to fulfill : sustainability and impacl 3.2 In order to be sustainable the programme must have: a sufficient human resources with critical mass and generation cohorts, b research funds from multiple sources and continuing programmes, c physical facilities including buildings, laboratories, equipment and support resources, d networking within USM and externally with other research institutions. 3.3 The impdCt of research was assessed on: a publications b patents/! P/products/copyrights c training and technology transfer d consultancy e policy and regulatory implications f awards and honours